Survival and prognostic factors of hospitalized acute myocardial infarction patients in district of Kota Bharu, Kelantan : a retrospective cohort study 2000-2003 - Aziz, Aniza Abd. (2006)
INTRODUCTION Acute n1yocardial infarction (AMI) ren1ains a major public health problen1 in Malaysia despite advances in medical management and technology. Local prognostic data on AMI will provide an essential information for effective preventive measures. The objectives of the study were to determine the survival of hospitalized acute n1yocardial infarction patients in Kota Bharu and identify the prognostic factors that influence the risk of death. METHODOLOGY A retrospective cohort study was conducted involving 368 hospitalized AMI patients from the district of Kota Bharu who were adtnitted in two tet1iary hospital; Hospital Kota Bharu and Hospital Universiti Sains Malaysia from I st January 2000 to 3I st Decetnber 2003. Additional follow up of one year after the recruittnent of the subjects was done fron1 I st January 2004 to 3I st Decen1ber 2004. All patients who fulfilled the criteria were included in the study. Hospital tnedical records and physician clinic records \Vere reviewed by a researcher. The required inforn1ation on variables of interest and patients· survival status until 31st December 2004 was recorded into a data collection forn1. Telephone calls were also conducted to obtain the inforn1ation on survival status of son1e patients who were discharged alive but loss to follow up. RESULTS The overall cumulative survival for hospitalized AMI in Kota Bharu were 91.0 (95o/o confidence interval (CI): 87.6~ 93.5), 88.8 (95% CI: 85.2., 91.7)~ 86.6 (95o/o CI: 82.6~ 89.7) and 83.9 (95% CI: 79.6, 87.5) percent for I day, 2 days, I week and I tnonth respectively. The long-term survival rate for 6 months, I year, 2 years~ 3 years and 4 years after AMI were 80.7 (95% CI: 76.1. 84.6), 77.5 (95% CI: 72.6~ 81.7)~ 76.2 (95% CI: 71.2. 80.6)~ 71.9 (95% CI: 66.0, 76.9) and 69.2 (95% CI: 62.7~ 74.8) percent respectively. Based on Cox Proportional Hazards Regression multivariable analysis after adjusting other variables, the significant prognostic factors that influenced the risk of death in hospitalized acute myocardial infarction patients in Kota Bharu were age at diagnosis (HR=I.03. 95% CI: 1.01. 1.06). diabetes n1ellitus (HR=l.60, 95% CI: 1.03~ 2.46), left ventricular failure (HR=2.15, 95% CI: 1.38, 3.34 ). thron1bolytic therapy (HR=0.48. 95°/o CI: 0.3 L 0.73) and first contact of care (HR=0.47. 95% CI: 0.24. 0.91 ). CONCLUSION Survival rate of hospitalized AMI patients in the district of Kota Bharu was con1parable with other developed countries. All significant independent prognostic factors identified were considerably similar to other countries. except a few itnpot1ant factors such as gender and drugs prescribed on discharge. Interestingly. first site contact of n1edical care was also identified to significantly influence the risk of death of AMI in Kota Bharu.